Analisis Statis Konstruksi dan Lance Tube Sootblower Tipe Motorised Rotary Menggunakan Software Solidworks 2016 - Felani, Ahmad; Al-Janan, Dony Hidayat (Jurnal Rekayasa Mesin, 2021)
Sootblower is a boiler support equipment that works to clean soot. Sootblower requires a strong construction to support the components in order to work optimally. Sootblower is also not free from several failures on its components, the main component that causes failure on the sootblower is the lance tube. This study aims to analyze the static construction and lance tube motorized rotary sootblower type sootblower using Solidworks software. The method used in this research is a simulation based on the finite element method. The material applied to the construction is St 37 and the material on the lance tube is ASTM A213 T92. The static simulation results show that the construction design of the angle iron measuring 35Ã—35Ã—6 mm has a max stress value of 57,50 N/mm2 that occurs in the bolt hole, a value of max displacement of 0,0146 mm on the rod supporting the bearing, and a factor of safety value of 4,08 so it is safe to use. Static simulation on the design of 40 NB diameter lance tube with four thickness variations shows the highest max stress value, the highest max displacement, and the lowest factor of safety occurs in the lance tube thickness of 10,2 mm, which has a max stress value of 276,24 N/mm2, max displacement of 335,53 mm and a factor of safety 1,59. Lance tubes with a thickness of 10,2 mm can be declared safe because the value of the factor of safety meets the minimum limit for static loading.